Intelligent Disease Diagnosis: A Multi-Disease Prediction Approach Using Machine Learning - Anjali Yadav; Shruti Dwivedi; Anubhav Dwivedi; Ujjwal Thakur; Dr. Nikhat Akhtar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Diseases prediction, which seeks to pinpoint persons at risk of developing particular illnesses, is an essential aspect of healthcare. Recently, machine learning algorithms have shown to be excellent instruments in sickness prediction, owing to their exceptional capacity to analyse extensive datasets for intricate patterns. The advancement of Machine Learning (ML) in modern healthcare has generated novel potential for the detection and treatment of chronic diseases. This study provides a comprehensive Multiple Disease Prediction System that accurately predicts diabetes, cancer, and heart disease via machine learning techniques. The system aims to analyse complex medical information to identify patterns and risk factors associated with these diseases. The system employs cardiovascular data analysis and logistic regression to identify heart illness and provide a probabilistic assessment of cardiac health. Convolutional Neural Networks, which analyse medical imaging to identify malignancies with high accuracy, are used to enhance cancer diagnosis. Support Vector Machines are used to forecast diabetes by considering many metabolic and genetic variables for assessment. The objective of this initiative is to assist individuals in identifying their health concerns just by their symptoms and precise vital signs. The suggested methodology demonstrates that the system is exceptionally precise and efficient, providing a significant decision support tool for physicians and health-conscious consumers.